The challenge of Núcleo de Atenção Médica Integrada in view of the need to include the speech-language pathologist in Fortaleza’s Municipal Health System - Silva, Maria Emília Macedo Lopes; Brasil, Christina Cesar Praça; Regis, Aretuza Carla da Fonseca (Saúde e Sociedade, 2010)
PURPOSE: To demonstrate the need to include the speech-language pathologist and audiologist in the municipal health system of the city of Fortaleza (Northeastern Brazil), due to the high demand of patients and the lack of public speech-language and audiology services in the city. METHODS: Documental, cross-sectional and descriptive study with a quantitative approach, developed between July and September 2008. Data were collected through the analysis of the records of the speech-language and audiology assistance provided for patients at NAMI-Unifor (The Medical Care Nucleus of the University of Fortaleza) in the period from January 2006 to December 2007. RESULTS: There was predominance of the assistance provided for the age groups between 0 and 6 years old in the audiology service (22.05%) and 0 to 10 years old in the speech-language therapy service (58.09%). The most applied audiology procedure was audiometry (65.78%), and the main professional responsible for referring patients to the audiology service was the otorhinolaryngologist (56.39%). In speech-language therapy, oral language and/or writing was the area with the highest prevalence of visits (36.99%). Group therapy reached a significant percentage: 37.27% in 2007. A fall in the number of visits during the University's recess period was observed, due to the reduction in the number of students who are responsible for the procedures. CONCLUSION: With work in the level of primary care as regards the health of human communication/deglutition, there would be a reduction in public expenses with the treatment of speech-language and audiology alterations in the other health care levels. The presence of the speech-language therapist in the Primary Care Units would help to improve the quality of life of the population across the whole life cycle, and would also reduce the burden in the public services that provide speech-language therapy in the city of Fortaleza.